On a problem of development of microbiological agents (fungicides and fertilizers) for conditions of the Northeast of the European part of the Russian Federation - O. V. Ryabova (Аграрная наука Евро-Северо-Востока, 2016)
Topic areas of research in the design of microbiological agents to plant industry and crop farming are formulated taking into account the specific soil and climatic conditions, characteristics of agricultural production and phytosanitary condition of crops in the North-East of the European part of Russia, as well as on the basis of the analysis of the Russian market of biopesticides in the region. Term "microbiological preparations" in this article is used for means which active basis are living cells of beneficial microorganisms. The key moments in the development of new microbial agents for use in the specific conditions of the region under study are the following: creation of new drugs should be based on microbial agents adapted to the given conditions. Polyfunctional association of microorganisms resistant to high soil acidity, low environment temperature, and soil drought that contribute to protection of plants against pathogens, enriching soil with available to plants biological nitrogen, as well as phosphorus and potassium have become a base of drugs. Urgent is the development of micro-biological preparations for protection of perennial grasses, oats and rye. At the absence of bio-fungicides against brown spot, askohitosis, anthrac-nose, rust of perennial grasses, as well as snow mold, ergot, Alternaria (on grain), brown leaf rust of cereals study of possibilities of its creating has scientific and practical interest.